2017
DOI: 10.1590/0103-6440201700525
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Bioactivity of Calcium Silicate Cements Combined with Niobium Oxide in Different Cell Lines

Abstract: The aim of this study was to evaluate the cytotoxicity and bioactivity of calcium silicate-based cements combined with niobium oxide (Nb2O5) micro and nanoparticles, comparing the response in different cell lines. This evaluation used four cell lines: two primary cultures (human dental pulp cells - hDPCs and human dental follicle cells - hDFCs) and two immortalized cultures (human osteoblast-like cells - Saos-2 and mouse periodontal ligament cells - mPDL). The tested materials were: White Portland Cement (PC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…Rodr ıguez-Lozano et al Acidic environment and root repair cements International Endodontic Journal, 52, 1196-1209 rather than bismuth oxide and it is Fe-free. This result was consistent with a previous report showing that tantalum oxide promotes physicochemical properties such as adequate radiopacity and calcium hydroxide production (Tanomaru-Filho et al 2017). In addition, the presence of tantalum oxide in bioactive cements stimulated alkaline phosphatase activity and mineralization formation (Quintana et al 2018).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Rodr ıguez-Lozano et al Acidic environment and root repair cements International Endodontic Journal, 52, 1196-1209 rather than bismuth oxide and it is Fe-free. This result was consistent with a previous report showing that tantalum oxide promotes physicochemical properties such as adequate radiopacity and calcium hydroxide production (Tanomaru-Filho et al 2017). In addition, the presence of tantalum oxide in bioactive cements stimulated alkaline phosphatase activity and mineralization formation (Quintana et al 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Correlating the cell viability assays with the cell migration data, similar values of cell migration to the control at pH 5.2 were observed, but lower cell migration rates than the control at pH 7.4. Previous studies with other MTAbased cements displayed osteoinductive potential and good biocompatibility when used as root-end filling materials in the medullary bone of rabbits (Chen et al 2015, Mestieri et al 2017. However, the lack of previous reports evaluating the biological properties of NeoMTA-Plus and Endocem-MTA exposed to an acidic environment may be considered a limitation of the present study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…ALP activity increased at 3 and 7 days of cells exposure to the calcium silicate cements, as has been demonstrated in previous studies with the Saos‐2 cell line (Mestieri et al . , Tanomaru‐Filho et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have also shown that the addition of niobium into biomaterials do not result in cytotoxicity. These investigations include tests with different materials, such as fluorapatite glass‐ceramics (Kushwaha et al, ), phosphate glasses (Minghui, Wenchuan, Jun, et al, ), and bioactive glass‐niobium granules (Fernandes et al, 2012) hydroxyapatite bioceramics (Capanema et al, ) and calcium silicate cements with different cell lines (Mestieri et al, ). In one of these assays, human osteogenic cells (SAOS) were incubated with Nb‐doped hydroxyapatite for 72 h and cell viability was tested by means of a MTT assay.…”
Section: Resultsmentioning
confidence: 99%